ANALISIS TAHANAN HORIZONTAL TIANG PANCANG BARU YANG DIBEBANI LATERAL AKIBAT EFEK ADANYA TIANG PANCANG EKSISTING PADA TANAH CLAY - Fardan Fikriansyah; Budi Susilo Soepandji (Racic : Rab Construction Research, 2024)
The method of driving new piles in existing buildings using existing piles is often used to speed up the construction period. The load distribution and displacement of the new pile need to be investigated further because of the influence of the existing pile. The lateral load displacement method (p-y curve) is used to analyze the load and displacement of the pile using threedimensional finite element analysis. The new and existing piles used are piles with a diameter of 0.6 meters, a thickness of 0.1 meters, a pile depth of 17 meters, and the distance between the new piles and the existing piles is 1 meter. The horizontal load applied is 150 kN on the pile head which is 1 meter from the ground surface. This research was carried out on clay with the Modified Cam Clay constitutive model. The results of three-dimensional finite element analysis show that the horizontal resistance of the new pile increases at the pile head due to the presence of the existing pile.